Moderasi Norma Sosial dan Keterlibatan Personal terhadap Perilaku Peduli Lingkungan - Yogi Pambudi; Ni Putu Pristi Wisuantari (Jurnal Psikologi Teori dan Terapan, 2021)
Pro-environmental behavior is a solution to overcome environmental problems. Plastic straw waste, which was produced majorly from restaurants consumption, has been identified as one of the causes of the environmental damage. This research was conducted to examine the moderation effect of social norms to plastic straw usage among restaurant visitors. The uantitative method was used by using self-report questionnaires to measure descriptive norm, injunctive norm, and personal involvement. Data were collected from 106 respondents whose ages ranged from 18 to 54 years with the proportion of 44% male and 66% female. This study has four hypotheses, namely the injunctive norm moderates the relationship between descriptive norm and pro-environment behavior, personal involvement moderates the relationship between descriptive norm and pro-environmental behavior, descriptive norm moderates the relationship between injunctive norm and pro-environmental behavior, and personal involvement moderates the relationship between injunctive norm and pro-environmental behavior. Statistical analysis using IBM SPSS with the add-on PROCESS Hayes 3.4 was used to test the moderation effect. The study found that there are no significant results from the four hypotheses. Although all hypotheses were not proven, the descriptive norm was proved to have a moderation effect to relationship between the injunctive norm and pro-environmental behavior when the score of descriptive norms is moderate or high. Hence, injunctive norm has potential to increase pro-environment behavior when it is moderated by moderate or high levels of descriptive norm.Keywords: Descriptive norm, injunctive norm, personal involvement, pro- environmental behavior Abstrak: Perilaku peduli lingkungan adalah solusi untuk mengatasi masalah lingkungan. Salah satu penyebab masalah lingkungan dengan begitu banyaknya sampah sedotan plastik. Penelitian ini menguji interaksi moderasi dari norma sosial dan keterlibatan personal terhadap perilaku peduli lingkungan pada pengunjung restoran terkait penggunaan sedotan plastik. Penelitian ini menggunakan metode kuantitatif terhadap 106 responden dengan rentang usia dari 18 54 tahun dan proporsi gender pria 44% dan perempuan 66%. Instrumen yang digunakan adalah alat ukur norma deskriptif, norma injungtif, dan keterlibatan personal. Penelitian ini menguji empat hipotesis, yakni; norma injungtif memoderasi norma deskriptif terhadap perilaku peduli lingkungan, keterlibatan personal memoderasi norma deskriptif terhadap perilaku peduli lingkungan, norma deskriptif memoderasi norma injungtif terhadap perilaku peduli lingkungan, dan keterlibatan personal memoderasi norma injungtif terhadap terhadap perilaku peduli lingkungan. Analisis statistik menggunakan IBM SPSS dengan add-on PROCESS Hayes 3.4 untuk melihat efek moderasi tersebut. Hasilnya, keempat hipotesis tidak terbukti. Meskipun keempat hipotesis ditolak tetapi norma deskriptif, ketika berada nilai moderat dan tinggi, memiliki pengaruh interaksi dalam memoderasi peran norma injungtif terhadap perilaku peduli lingkungan, Sehingga norma injungtif yang dimoderasi oleh norma deskriptif berpotensi untuk meningkatkan perilaku peduli lingkungan.